Bees biodiversity, forage behavior and fruit production in gherkin crop (Cucumis anguria L.) - Darclet Teresinha Malerbo-Souza; Milena Oliveira de Andrade; Rodrigo Alves de Siqueira; Núbia Maria Guedes de Medeiros; Lucas Rodrigues de Farias; Thulio Gustavo da Silva; Lucas Delano Sousa Nascimento; André Carlos Silva Pimentel (Acta Scientiarum. Animal Sciences, 2019)
The objectives were to evaluate the biodiversity of bees, forage behavior and their effect on fruit production in the gherkin crop (Cucumis anguria L.) in the campus of the University Center Moura Lacerda in two years. The frequency and type of collection of the insects in the flowers was observed by counting from 8:00 a.m. to 5:00 p.m., in the first 10 minutes of each time, for three distinct days in each year. The percentage of fruiting was quantified in 25 female flowers covered with nylon compared to the 25 female flowers uncovered in the two years. The flowers were visited by the Africanized honey bees Apis mellifera and the native bees Plebeia sp., Exomalopsis sp. and Melissodes sp., and the Africanized honey bees presented higher frequency and constancy with a higher number of visits in the male flowers compared to the female ones and these visits occurred between 8:00 a.m. and 3:00 p.m. Without the visitation of the bees there was no fruit production, and both the Africanized honey bee and the native ones when collecting nectar and pollen, visited both female and male flowers, carrying pollen in their body, being considered important pollinators of this culture.